TAN MALAKA'S TRACK RECORD IN TANAH DELI: A CASE STUDY OF SENEMBAH MAATSCHAPPIJ (1919-1921) - Azwar, Muhammad Revan; Syam, Abdi Mubarak (International Journal of Cultural and Social Science, 2025)
This study analyzes the transformation of colonial education into an instrument of class resistance by Tan Malaka on the Senembah Maatschappij plantation, Deli (1919–1921). Using a micro-historical approach and triangulation of primary sources (Tan Malaka's autobiography, Leiden archives, Benih Merdeka newspaper) and secondary sources (historiography, critical pedagogy studies), this study reveals pedagogical strategies based on the synthesis of Marxist principles, especially the critique of capitalist exploitation and Islamic values ??of social justice ('adl). The results of the study show three mechanisms of curriculum decolonization: integration of teaching materials with structural realities (low wages, poenale sanctie), substitution of authoritarian teaching with reflective dialogue, and the elimination of physical punishment as resistance. The conflict with the plantation elite represents the dialectic of colonial hegemony (Ethical Politics) versus educational counter-hegemony. Multi-ethnic interactions in the classroom strengthen Tan Malaka's vision of internationalism which would later be realized in PARI (1927) and the Jakarta Manifesto (1945). This study contributes to the affirmation of education as a locus of resistance that is often neglected in Indonesian historiography, the synthesis of Islam-Marxism as a framework for epistemic decolonization, and the relevance of pedagogy based on socio-historical reality to dismantle contemporary inequality. Its practical implications offer a critical-transformative education model as a liberation praxis.